Cranial ontogeny in the Puma lineage, Puma concolor, Herpailurus Yagouaroundi and Acinonyx jubatus (Carnivora: Felidae): a three dimensional geometric morphometric approach - Segura, Valentina (2013)
The Puma lineage is a monophyletic group that includes three living species: Puma concolor, Herpailurus yagouaroundi, and Acinonyx jubatus. It has been analysed from ecological and taxonomic perspectives, but their cranial ontogeny has been poorly studied. In this study, we assessed the cranial shape and size variation through three-dimensional geometric morphometric techniques, and explored the acquisition of definitive shape and size in relation to key life-history events. Each species occupied different locations in the shape morphospace: A. jubatus and P. concolor showed shorter and wider skulls, with more expanded zygomatic arches, than H. yagouaroundi, which presented the most divergent pattern of change. Ontogeny was more similar between P. concolor and A. jubatus than between the closely related P. concolor and H. yagouaroundi. The evolution of ontogenetic change in the lineage seems to be more influenced by size. Changes detected between juvenile and adult skulls enhanced predatory skills, coincident with the change from a diet of milk to a carnivorous diet. Change patterns suggest that the skull is not morphologically conservative in the lineage, in contrast with other carnivores such as canids and hyaenids. The enlargement of the rostrum observed in some canids and the reinforcement of the bite mechanism of hyaenids were not detected in this group.